端粒与端粒酶研究在肺癌中的临床应用前景与挑战 (Zhongguo Fei Ai Za Zhi, 2021)
Lung cancer is one of the malignant tumors with high incidence rate and high mortality worldwide. Telomere and telomerase are closely related to the occurrence and development of lung cancer. Although telomerase may not be the direct cause of carcinogenesis, it plays a key role in maintaining telomere length and tumor growth. The length of most tumors, including lung cancer, is shortened. The change of telomere length is related to the risk of lung cancer, and may become the therapeutic target and predictive index. Target drugs for telomere and telomerase signaling pathway are constantly being explored, and drugs represented by telomerase inhibitors are expected to be used in clinical treatment of lung cancer in the future. However, the research on telomere and telomerase is far from enough. The bypass mechanism of telomere length maintenance may be the direction of further research.